Commitment in marketing research services: two alternative models - Čater, Barbara; Žabkar, Vesna; Čater, Tomaž (Journal of Business Economics and Management, 2011)
The paper aims to contribute to the body of knowledge on client commitment in business-to-business professional services by developing and testing two alternative models: one based on the Relationship Marketing (RM) approach and the second on the Industrial Marketing and Purchasing Group (IMP) approach. Both models include the same mediators (components of commitment) and consequences (attitudinal and behavioral loyalty), yet they differ in the antecedents of commitment. By using SEM, both models are tested and compared on a sample of 150 firms. The results show that affective commitment is the only component of commitment that influences both attitudinal and behavioral loyalty. In the RM model affective commitment is positively influenced by trust, social bonds and satisfaction, while in the IMP model it is positively influenced by trust and knowledge transfers. Although differences in the sizes of effects can be found, the two models perform comparably well in terms of the model fit and their explanatory power of loyalty. Article in English. Įsipareigojimai atliekant rinkodaros tyrimus: du alternatyvūs modeliai Santrauka. Straipsnio tikslas - nustatyti žinių lygį, kurį yra pasiekę profesionalai, organizuojantys paslaugų teikimą pagal modelį verslas verslui. Autoriai pasirinko du modelius: vienas pagrįstas rinkodaros ryšių (MR), kitas – gamybinės rinkodaros ir prekybos grupių (IMP) požiūriu. Abu modeliai apima tokius parametrus, kaip įsipareigojimai, ir tokius rezultatus, kaip vartotojų lojalumas, požiūris, tačiau skirtingas pradines sąlygas. Atliekant tyrimus modeliai buvo pritaikyti 150 įmonių. Kaip teigia straipsnio autoriai, gauti tyrimo rezultatai rodo, kad emocinis įsipareigojimas yra sudėtinė įsipareigojimų, turinčių įtakos lojalumui bei vartotojų požiūrio formavimui, dalis. Pritaikius pasirinktus modelius gaunami atitinkami rezultatai. Reikšminiai žodžiai: įsipareigojimas, rinkodara, rinkodaros tyrimai, verslas verslui.